Development of a system generator for Marsohod development boards. (February 2019) - Dmitriy, P; Alexey, I; Romanov, A
Abstract: This article describes a technical solution of the system generator of configuration files of development boards "Marsohod 2", "Marsohod 2bis", "Marsohod 3", "Marsohod 3bis" for Quartus Prime software. The solution includes a web interface for the system generator, generation of configuration files, introduction of additional modules into the generated project, such as a frequency divider, Uart8 (RS-232), a module for preventing of contact bounce, and several types of simplest MIPS processor cores. This technical solution improves the convenience and speed of FPGA development, as well as reduces its entry threshold which can be significant for starting developers.